Job satisfaction as a pathway: examining the effects of transformational leadership and motivation on employee performance - Effendy, Sofan; Hidayah, Nur; Basalamah, Muhammad Ridwan (JURNAL MANAJEMEN MOTIVASI, 2025)
This study aimed to analyze the effect of transformational leadership and work motivation on employee performance through job satisfaction as a mediating variable at the Faculty of Humanities UIN Maulana Malik Ibrahim Malang. The research sample consisted of 250 employees who were given a questionnaire via WhatsApp via the Google Forms link, using a 5-point Likert scale to measure respondent agreement with the statement. The data analysis technique used Smart PLS (Partial Least Square) software. The results of this study indicate that transformational leadership has a significant effect on job satisfaction, work motivation has a significant effect on job satisfaction, transformational leadership has a significant effect on employee performance, work motivation has a significant effect on employee performance, job satisfaction has a significant effect on employee performance, transformational leadership has a significant effect on employee performance through job satisfaction, work motivation has a significant effect on employee performance through job satisfaction. This study shows that employee performance is, directly and indirectly, influenced significantly by transformational leadership and work motivation using a strong mediating variable of job satisfaction. This means that leadership style and motivation levels must be improved for employee job satisfaction and performance to increase. This study provides implications for institutional leaders to encourage a transformational leadership style, develop work motivation improvement programs, and build a work environment that supports job satisfaction.